(untitled) (Discourse of Law and Administration, 2024)
The study presents and analyses basic issues related to the legal regulation of the harvest assistance agreement and its practical significance. In addition to determining the legal nature of the harvest assistance contract and the resulting characteristic features of the established legal relationship, the study also referred to the age of the farmer’s helper, the remuneration to which the helper is entitled and the permissible scope of this type of contract. The effects of concluding an agreement on harvest assistance in the area of social security have not been ignored.